Child-appealing packaged food and beverage products in Canada-Prevalence, power, and nutritional quality. - Christine Mulligan; Laura Vergeer; Monique Potvin Kent; Mary R L'Abbé (PLoS ONE, 2023)
Background Children are frequently exposed to marketing on food packaging. This study evaluated the presence, type and power of child-appealing marketing and compared the nutritional quality of child-appealing vs. non-child-appealing Canadian packaged foods and examined the relationship between nutrient composition and marketing power. Methods Child-relevant packaged foods (n = 5,850) were sampled from the Food Label Information Program 2017 database. The presence and power (# of techniques displayed) of child-appealing marketing were identified. Fisher's Exact test compared the proportion of products exceeding Health Canada's nutrient thresholds for advertising restrictions and Mann Whitney U tests compared nutrient composition between products with child- /non-child-appealing packaging. Pearson's correlation analyzed the relationship between nutrient composition and marketing power. Results 13% (746/5850) of products displayed child-appealing marketing; the techniques used, and the power of the marketing varied ([Formula: see text] 2.2 techniques; range: 0-11). More products with child-appealing packaging than with non-child appealing packaging exceeded Health Canada's thresholds (98% vs. 94%; p < .001). Products with child-appealing packaging (vs. non-child-appealing) were higher in total sugars (median: 14.7 vs. 9 g/RA; p < .001) and free sugars (11.5 vs. 6.2 g/RA; p < .001), but lower in all other nutrients. There was weak overall correlation between marketing power and nutrient levels. Results varied by nutrient and food category. Conclusions Unhealthy products with powerful child-appealing marketing displayed on package are prevalent in the food supply. Implementing marketing restrictions that protect children should be a priority.